Paraphilic Disorder and Gender Dysphoria in a Case with High-Functioning Autism Spectrum Disorder - U. Altunoz; J. Krueger; M. Ziegenbein (European Psychiatry, 2022)
Introduction Autism spectrum disorder (ASD) is a neurodevelopmental disorder characterized with difficulties in social interaction/communication, restricted interests, and repetitive behaviors. Sexual issues such as paraphilic behaviors in ASD have gained attention in recent years, however there is still a great paucity of research regarding this issue.